Subspace-Based Range-Angle Tracking for Coherent FDA Radar - Sun, Yan; Wang, Wen-Qin; Greco, Maria Sabrina; Gini, Fulvio (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2025)
As an extension of the phased-array (PA) and frequency diverse array multi-input multi-output (FDA-MIMO) radars, the coherent FDA (C-FDA) radar simultaneously enjoys the merits from a higher coherent array gain and range-dependency, especially the range-angle decoupling. Based on these properties, C-FDA radar is potential to implement more robust target tracking. This paper proposes a subspace-based range-angle tracking method, including the subspace tracking and range-angle estimation. We first design a data processing structure for C-FDA radar, separating the range-dependent data from the angle-dependent data. Then we use the exponential decay function inspired from the information geometry to achieve fast convergence for the subspace tracking. Numerical results describe the range-angle tracking trajectories of C-FDA radar by using the proposed algorithm, indicating its superiority through the root mean square error (RMSE) and the subspace estimation performance (SEP).